DAMPAK KOMPENSASI, BEBAN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. X - Dyna Arofatul; Kustini Kustini (MANAJEMEN DEWANTARA, 2025)
Compensation is a form of company to help improve the standard of living of employees. Workload is the extent to which the individual potential of employees is desired in fulfilling all responsibilities. The work environment is all aspects both external and internal that are around employees. This study aims to analyze the effects of compensation, workload, and work environment on performance at PT. X. The research method is quantitative. The population in this study consists of 45 employees. For the sampling technique using the saturation sampling method, the data analysis technique used in this study uses Structural Equation Modeling (SEM) based on Partial Least Square (PLS) operated with Smart PLS version 3. From the results of the study a proven that: (1) compensation has a positive and significant effect on employee performance, (2) workload has a positive and significant effect on employee performance, (2) positive and significant effect on employee performance.